2012
DOI: 10.1161/circheartfailure.111.964494
|View full text |Cite
|
Sign up to set email alerts
|

Bisoprolol Delays Progression Towards Right Heart Failure in Experimental Pulmonary Hypertension

Abstract: Background-In pulmonary arterial hypertension (PH), sympathetic adrenergic activity is highly elevated. Sympathetic overactivity is a compensatory mechanism at first, but might be detrimental for cardiac function in the long run. We therefore investigated whether chronic low-dose treatment with bisoprolol (a cardioselective ␤-blocker) has beneficial effects on cardiac function in experimental PH. Methods and Results-PH was induced in rats by a single injection of monocrotaline (60 mg/kg). Pressure telemetry in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
137
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 182 publications
(156 citation statements)
references
References 40 publications
13
137
1
3
Order By: Relevance
“…As mentioned before, it has been proposed that maladaptive RVH is characterized by capillary rarefaction, 16 myocardial ischemia, 19 fibrosis, 2,20 and cardiomyocyte apoptosis, 2 and more recently it has been reported that the dysfunctional RV is characterized by significant metabolic remodeling and mitochondrial dysfunction. 21 These molecular and cellular changes are associated with a decrease in cardiac output, marked RV dilatation, and decreased exercise capacity.…”
Section: The Lung Circulation-rv Axismentioning
confidence: 95%
See 1 more Smart Citation
“…As mentioned before, it has been proposed that maladaptive RVH is characterized by capillary rarefaction, 16 myocardial ischemia, 19 fibrosis, 2,20 and cardiomyocyte apoptosis, 2 and more recently it has been reported that the dysfunctional RV is characterized by significant metabolic remodeling and mitochondrial dysfunction. 21 These molecular and cellular changes are associated with a decrease in cardiac output, marked RV dilatation, and decreased exercise capacity.…”
Section: The Lung Circulation-rv Axismentioning
confidence: 95%
“…Bogaard et al 18 demonstrated that treatment with the nonselective adrenergic blocker carvedilol improved maladaptive RVH functionally and histologically without affecting the lung circulation, and similar effects have been demonstrated utilizing other adrenergic receptor blockers. 19 More recently, Piao et al 12 evaluated the role of adrenergic desensitization in RVF and demonstrated that G protein-coupled receptor kinase 2 mediated an uncoupling of β-adrenergic receptor signaling, therefore impairing inotropic reserve. A particularly interesting finding from this study is that, at least in rats, downregulation of the β1, α1, and dopamine 1 receptors was partially independent of pressure overload.…”
Section: The Lung Circulation-rv Axismentioning
confidence: 99%
“…11 In addition, in PAH animal models β-blockers clearly have beneficial effects. [42][43][44] Why, then, has there not been an attempt to develop an antiadrenergic therapeutic strategy in PAH, where the status of the RV function is a major Figure 6. Chamber-specific norepinephrine (NE) and neuropeptide Y (NPY) depletion in failing right ventricles (RVs) from patients with pulmonary arterial hypertension (PAH).…”
Section: Could An Antiadrenergic Treatment Be Effective In Rvf Due Tomentioning
confidence: 99%
“…β blockade using carvedilol has been shown to reverse RV remodelling and maladaptive RV hypertrophy and improve RV function in experimental rats, similar to its effect on the left ventricle [9,10]. In addition, bisoprolol has been found to delay RV failure and preserve RV function in experimental pulmonary hypertension [11]. Patients with PAH are also known to have a high prevalence of left ventricular diastolic dysfunction [12], where β blockade may produce a salutary effect.…”
Section: Introductionmentioning
confidence: 96%